2016
DOI: 10.1002/macp.201600170
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Unexpectedly Rapid Degradation of Dihydroxyacetone-Based Hydrogels

Abstract: Biodegradable hydrogels are an important class of biomaterials with a diverse range of applications. In some cases, a rapid hydrogel degradation rate is advantageous. Polycarbonate hydrogels based on dihydroxyacetone (DHA), a natural metabolite, have been reported to undergo surprisingly fast hydrolytic degradation. In the present work, insight into the key features of DHA that contribute to the observed degradation rates is gained. In vitro degradation (mass loss) of three different chemically cross‐linked po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Dissolution of the dimer in protic solvents such as water and methanol shifts the solution equilibrium towards the monomer and allows for its isolation, although it reverts to the dimer upon storage. 9 However, these solvents prohibit the use of most organometallic 1,2-addition protocols. In order to deconvolute issues with the monomer/dimer equilibrium from potential issues with a 1,2-addition on a substrate with two unprotected hydroxy groups, our early studies used isolated 1,3-dihydroxyacetone monomer 15 as starting material.…”
Section: Scheme 4 Alternative Routes To Triolmentioning
confidence: 99%
“…Dissolution of the dimer in protic solvents such as water and methanol shifts the solution equilibrium towards the monomer and allows for its isolation, although it reverts to the dimer upon storage. 9 However, these solvents prohibit the use of most organometallic 1,2-addition protocols. In order to deconvolute issues with the monomer/dimer equilibrium from potential issues with a 1,2-addition on a substrate with two unprotected hydroxy groups, our early studies used isolated 1,3-dihydroxyacetone monomer 15 as starting material.…”
Section: Scheme 4 Alternative Routes To Triolmentioning
confidence: 99%
“…Based on the previous findings on DHA-containing poly (ester)s and poly(carbonate)s, it is apparent that these polymers show a rate higher than the expected rate of hydrolysis. 8,12 Neighboring group participation of β-carbonyls for Fig. 3 TGA-thermograms for poly(isosorbide) and poly(Iso-co-DHA).…”
Section: Hydrolytic Degradation Studymentioning
confidence: 99%
“…29,30 In a recent study by Ricapito et al on poly(ethylene glycol) (PEG) and poly (DHA) carbonate hydrogels, it was shown that having an extra methylene group on each side, in the case of 1,5-dihydroxypentan-3-one, provided significantly slower degradation compared to hydrogels formed with PEG and DHA-carbonates. 12 As the dilution study suggested, decreasing the polarity of the surrounding medium and decreasing the electron-withdrawing effect on the α-carbons limit the ability to form hydrates, which subsequently affects the hydrolytic degradation of the compound. In the polymer case, being confined to a hydrophobic micro-environment together with limited conformational mobility, chemical degradation rates are expected to be less pronounced.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
See 1 more Smart Citation
“…DHA is a natural product in human, bacteria, and plants metabolism and plays an important role in the research of new biomaterials, biological polymers and drug designs. The low toxicity of DHA (LD 50 = 160000 mg · kg –1 ) proposes hopefully comparable properties for nitrated derivatives. Based on the fact, that sugars can react with primary amines to form brown pigments, DHA, a three‐carbon sugar, can also react with amino acids .…”
Section: Introductionmentioning
confidence: 99%